2011
DOI: 10.1007/s11147-011-9065-6
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and hedge fund activism

Abstract: Hedge funds, Activism, Corporate governance, G11, G34,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 53 publications
10
96
6
Order By: Relevance
“…Although the activist hedge funds targeting large companies get lots of media coverage, it appears from our study, and as reported in several other studies (Brav et al, 2008;Aslan and Maraachlian, 2009; Greenwood and Schor, 2009; Klein and Zur, 2009;Boyson and Mooradian, 2011;Gantchev et al, 2015), that the median company targeted by activists is fairly small (market cap = US$148 million; revenues = $201 million).…”
Section: A Matched Random Samplesupporting
confidence: 71%
See 1 more Smart Citation
“…Although the activist hedge funds targeting large companies get lots of media coverage, it appears from our study, and as reported in several other studies (Brav et al, 2008;Aslan and Maraachlian, 2009; Greenwood and Schor, 2009; Klein and Zur, 2009;Boyson and Mooradian, 2011;Gantchev et al, 2015), that the median company targeted by activists is fairly small (market cap = US$148 million; revenues = $201 million).…”
Section: A Matched Random Samplesupporting
confidence: 71%
“…Many studies have been focusing on the impact of activists' 13D filing on the stock price of the targeted company over a short period of time (usually 20 days before and 20 days after). Indeed, there is ample evidence of 'abnormal' returns in a short period around the public disclosure of activism (Brav et al, 2008;Clifford, 2008;Brav et al, 2009;Greenwood and Schor, 2009;Klein and Zur, 2009;Boyson and Mooradian, 2011;Gow et al, 2014;Krishnan et al, 2015), and in Europe and Asia (Becht et al, 2014). Many observers interpret this jump in stock price on the appearance of an activist fund as evidence of shareholders valuing their brand of activism.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of hedge fund activism on target firms' performance has rigorously been discussed and studied in recent decades (Klein and Zur, 2006;Brav et al, 2008;Greenwood and Schor, 2009;Boyson and Mooradian, 2011;Bebchuk et al, 2014). The empirical findings of largely documented studies are consistent with the notion that fundrelated activism generates positively significant abnormal returns around the announcement of Schedule 13D Disclosures.…”
Section: Introductionmentioning
confidence: 80%
“…A general consensus exists among the researchers that the stock market favorably reacts to the announcement of a fund's involvement in a target firm, and as a result, generates positively significant abnormal returns (Klein and Zur, 2006;Brav et al, 2008;Boyson and Mooradian, 2011). In pre-crisis sample studies, Klein and Zur (2006) report 10.3% abnormal returns over a relatively longer (-30, +30) event window including the date of notification.…”
Section: Introductionmentioning
confidence: 99%
“…Activist hedge funds have been the most prominent and successful proponents of institutional shareholder activism in recent decades (Gillan & Starks, 2007). Boyson and Mooradian (2011) noted that the idea of hedge funds as activists is in direct contrast with their image as short-term, opportunistic investors. For example, in the early 2000s, prime brokerage operations of investment banks were very frequently the banks' only profitable divisions, due to heavy trading volume among their hedge fund clients.…”
Section: Iiic Active Monitoring By Shareholders -Ex Post Interventionmentioning
confidence: 99%